A borate-introduced molybdenum disulfide / nano zinc oxide composite lubricating material and a method for preparing a lubricating coating

The one-step hydrothermal method is used to prepare molybdenum disulfide/nano zinc oxide/borate composite lubricating material with in-situ doped heterojunction structures, and the lubricating coating is prepared by air spraying method, solving the existing high-temperature lubrication The problem of unstable lubrication performance of the material in an environment of 800℃ or above has achieved efficient high-temperature lubrication performance improvement.

CN117384690BActive Publication Date: 2025-02-18NORTHWESTERN POLYTECHNICAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311391132.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-25
Publication Date
2025-02-18
Estimated Expiration
2043-10-25

AI Technical Summary

Technical Problem

The lubrication performance of existing high-temperature lubricating materials is unstable in high-temperature environments of 800℃ or above, and it is difficult to meet the needs of complex environments such as high temperature, high pressure, high speed, high load-bearing and space particle radiation in space vehicles, etc.

Method used

The one-step hydrothermal method is used to prepare molybdenum disulfide/nano zinc oxide/borate composite lubricating material with in-situ doped heterojunction structures, and the lubricating coating is prepared by air spraying to enhance the high-temperature lubrication of the lubricating material. performance.

Benefits of technology

It significantly improves the high-temperature lubrication performance of the lubricating material above 800°C, enhances the bonding of the lubricating material and the matrix, and the preparation process is simple, easy to control, low cost, and easy to achieve.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117384690B_ABST
    Figure CN117384690B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of high-temperature lubrication, and specifically discloses a preparation method of a molybdenum disulfide / nano zinc oxide composite lubricating material and a lubricating coating introduced with borate, and the preparation method of the composite lubricating material comprises: preparing a MoS2 / nano ZnO composite material by a one-step hydrothermal method; ball-milling and mixing the MoS2 / nano ZnO composite material and borate to obtain a uniform mixed powder; dispersing the uniform mixed powder in a dispersing solvent, and ultrasonically stirring for 6 to 8 hours to obtain a uniform mixed solution; washing and drying the uniform mixed solution to obtain a molybdenum disulfide / nano zinc oxide / borate composite lubricating material. The borate binder phase introduced in the present invention can not only improve the bonding between the coating and the substrate, but also greatly improve the high-temperature lubrication performance of the lubricating material. The preparation method of the present invention has low reaction temperature, mild conditions, low energy consumption, simple and easy-to-control preparation process, low cost, short preparation cycle, and easy implementation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of high-temperature lubrication, and in particular relates to a borate-introduced molybdenum disulfide / nano zinc oxide composite lubricating material and a preparation method of a lubricating coating. Background Art

[0002] At present, the launch and operation of spacecraft and space vehicles are facing the development of repeatability, all-region, high speed and low cost. More and more key moving parts in the aerospace field need to face complex and changeable extreme working environments such as high temperature, high pressure, high speed, high load and space particle radiation, which puts higher requirements on the high temperature performance and high temperature lubrication of lubricating materials. Therefore, it is urgent and necessary to improve the high temperature lubrication performance of lubricating materials above 300℃, especially at around 800℃ and above, through appropriate preparation processes and methods.

[0003] Most of the existing high-temperature lubricating materials have limitations such as uncontrollable preparation process and unstable high-temperature lubricating performance. In particular, the problem of poor high-temperature lubricating performance at 800°C and above needs to be solved urgently. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a simpler method for preparing a lubricating material with excellent high-temperature lubrication performance, and more particularly relates to a high-temperature composite lubricating material of molybdenum disulfide / nano-zinc oxide / borate with a heterojunction structure in situ doped with nano-zinc oxide, which is prepared by a one-step hydrothermal method by introducing a borate binder phase.

[0005] Specifically, the first aspect of the present invention provides a method for preparing a borate-introduced molybdenum disulfide / nano zinc oxide composite lubricating material, comprising:

[0006] The MoS2 / nano ZnO composite material was prepared by a one-step hydrothermal method;

[0007] The MoS2 / nano ZnO composite material is mixed with borate by ball milling to obtain a uniform mixed powder;

[0008] Dispersing the uniformly mixed powder in a dispersing solvent, and subjecting the mixture to ultrasonic stirring for 6 to 8 hours to obtain a uniformly mixed solution;

[0009] The uniformly mixed solution is washed and dried to obtain a molybdenum disulfide / nano zinc oxide / borate composite lubricating material.

[0010] As a further illustration of the present invention, the borate is one of sodium borate and potassium borate; the dispersing solvent is one of ethylene glycol ethyl ether, xylene and acetone.

[0011] As a further illustration of the present invention, the parameters of the ball milling mixing are set as follows: the ball-to-powder ratio is 2:1, the rotation speed is 180-360 rpm, and the ball milling time is 4-6 hours.

[0012] As a further illustration of the present invention, the ball milling jar for ball milling and mixing is a stainless steel jar lined with tungsten carbide, and the grinding medium is a tungsten carbide hard alloy ball.

[0013] As a further illustration of the present invention, the diameter of the tungsten carbide hard alloy ball is 5 mm or 8 mm.

[0014] As a further illustration of the present invention, the drying conditions are: vacuum drying at 80-100° C. for 18-24 hours.

[0015] A second aspect of the present invention provides a method for preparing a lubricating coating, comprising:

[0016] The high-temperature alloy substrate that has undergone surface pretreatment is subjected to borate boration treatment to form a borate transition layer that is insoluble in water on the surface of the substrate;

[0017] Uniformly dispersing the molybdenum disulfide / nano zinc oxide / borate composite lubricating material prepared by any of the preparation methods described above to obtain a uniformly mixed composite lubricating material dispersion;

[0018] The composite lubricating material dispersion is air-sprayed to prepare a molybdenum disulfide / nano zinc oxide / borate composite lubricating coating.

[0019] As a further illustration of the present invention, the air spraying specifically comprises:

[0020] The substrate with the borate transition layer is preheated at 50-60°C for 30-40 minutes, while the spray gun air pressure is maintained at 0.6-0.7MPa and the spray gun caliber is 1-2mm. The preheated substrate is placed horizontally, the spray gun is 20-30cm away from the substrate, the tilt angle is 40-60°, the number of reciprocating times is 2-3 times, and the coating thickness is about 60μm.

[0021] As a further illustration of the present invention, the method further comprises:

[0022] After the coating is prepared, the substrate is placed in a vacuum drying oven at 60-80°C for 40-60 minutes and then transferred to a muffle furnace for curing at a curing temperature of 180-200°C for 60-80 minutes. After naturally cooling to room temperature, a molybdenum disulfide / nano zinc oxide / borate composite lubricating coating is obtained.

[0023] Compared with the prior art, the present invention has the following beneficial technical effects:

[0024] The borate binder phase introduced in the present invention can not only improve the bonding between the coating and the substrate, but also greatly improve the high-temperature lubrication performance of the lubricating material.

[0025] The preparation method of the present invention has low reaction temperature, mild conditions, low energy consumption, simple and easy-to-control preparation process, low cost, short preparation cycle and is easy to implement.

[0026] In the present invention, the antioxidant and high-temperature lubrication properties of the lubricating material can be synergistically improved through the combined effects of heterojunction structure optimization and chemical passivation of the edge dangling bonds of MoS2 by doping. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is an XRD diagram of the high-temperature lubricating material MoS2 / nano ZnO / sodium borate prepared by the method of the present invention;

[0028] Figure 2 is the friction coefficient curve of the high temperature lubricating material MoS2 / nano ZnO / sodium borate at 750°C in Example 1;

[0029] Figure 3 is the friction coefficient curve of the high temperature lubricating material MoS2 / nano ZnO / sodium borate at 775°C in Example 1;

[0030] Figure 4 This is the friction coefficient curve of the high temperature lubricating material MoS2 / nano ZnO / sodium borate at 800°C in Example 1. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] The present invention mainly introduces a borate binder phase, and prepares a high-temperature composite lubricating material of molybdenum disulfide / nano zinc oxide / borate with a heterojunction structure in situ doped with nano zinc oxide by a one-step hydrothermal method, which can be applied to the lubrication and protection of aerospace bearings, bushings, etc. Compared with the prior art methods, the preparation method of the present invention is simpler, has a short preparation cycle, and is easy to implement. Secondly, through the combined effect of heterojunction structure optimization and chemical passivation of the edge dangling bonds of MoS2 by doping, the anti-oxidation and high-temperature lubrication properties of the lubricating material can be synergistically improved. At the same time, the introduced borate binder phase can not only improve the bonding between the lubricating coating and the substrate, but also greatly improve the high-temperature lubrication performance of the lubricating material. It was found through tribological tests that the lubricating material prepared by the present invention still has good high-temperature lubrication performance above 800°C.

[0033] Specifically, the present invention provides a method for preparing a borate-introduced molybdenum disulfide / nano zinc oxide composite lubricating material, comprising the following steps:

[0034] Step 1: MoS2 / nano ZnO composite material is prepared by a one-step hydrothermal method;

[0035] Step 2: ball-milling the MoS2 / nano ZnO composite material and the borate to obtain a uniform mixed powder;

[0036] Step 3: Dispersing the uniformly mixed powder in a dispersing solvent, and obtaining a uniformly mixed solution by ultrasonic stirring for 6 to 8 hours;

[0037] Step 4: Wash and dry the uniformly mixed solution to obtain a molybdenum disulfide / nano zinc oxide / borate composite lubricating material.

[0038] Step 1 specifically includes:

[0039] First, ammonium molybdate and thiourea in a molar ratio of 1:1 are dispersed in a certain amount of deionized water, stirred for 30 to 50 minutes using a magnetic stirrer, and ultrasonically treated for 10 to 30 minutes until they are completely uniformly dispersed.

[0040] Then, a certain amount of ZnO nanoparticles (average particle size of 30±10 nm) was added according to the molar ratio of ammonium molybdate to nano-ZnO of 1:7-9, and then magnetic stirring was performed for 60-80 minutes, and ultrasonic treatment was performed for 40-60 minutes until the solution was fully mixed.

[0041] Finally, the mixed solution was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and stored in an oven at 200-220 °C for 24 h.

[0042] After it is cooled naturally to room temperature, it is washed with anhydrous ethanol and deionized water for multiple times, and the black precipitate is collected by filtration and centrifugation.

[0043] Finally, the MoS2 / nano ZnO composite material is obtained by vacuum drying it at 60-80°C for 12-18 hours.

[0044] The borate in step 2 is sodium borate, potassium borate, etc.; the ball milling jar for ball milling is a stainless steel jar lined with tungsten carbide, the grinding medium is a tungsten carbide hard alloy ball, and the diameter of the tungsten carbide hard alloy ball is 5mm or 8mm. The parameters of ball milling are set as follows: the ball-to-powder ratio is 2:1, the rotation speed is 180-360rmp, for example, 180rmp, 220rmp, 260rmp, 300rmp, 360rmp, etc.; the ball milling time is 4-6 hours, for example, 4 hours, 5 hours, 6 hours, etc.

[0045] In step 3, the dispersing solvent is ethylene glycol ethyl ether, xylene, acetone, etc., and the ultrasonic stirring time can be, for example, 6 hours, 7 hours, 8 hours, etc.

[0046] The uniformly mixed solution in step 4 is repeatedly washed with deionized water and anhydrous ethanol; the drying conditions are: at 80-100°C, for example, 80°C, 90°C, 100°C, etc.; vacuum drying for 18-24 hours, for example, 18 hours, 20 hours, 22 hours, 24 hours, etc.

[0047] The method for preparing a lubricating coating using the above-mentioned molybdenum disulfide / nano zinc oxide / borate composite lubricating material comprises the following steps:

[0048] Step 1: subjecting the surface pretreated high-temperature alloy substrate to a borate borate treatment to form a water-insoluble borate transition layer on the substrate surface;

[0049] Step 2: uniformly dispersing the molybdenum disulfide / nano zinc oxide / borate composite lubricating material prepared by any of the above preparation methods to obtain a uniformly mixed composite lubricating material dispersion;

[0050] Step 3: Prepare the molybdenum disulfide / nano zinc oxide / borate composite lubricating coating by air spraying the composite lubricating material dispersion.

[0051] The surface pretreatment process in step 1 specifically includes: using wire cutting to cut the 718 high-temperature alloy substrate into several 30*5*2mm substrates, and then grinding them with 200 mesh, 400 mesh, 600 mesh and 1000 mesh sandpaper until there are no scratches, ultrasonically cleaning with acetone and anhydrous ethanol to remove oil and other impurities and drying, and then sandblasting the substrate surface.

[0052] The boronization treatment in step 1 can form a borate transition layer that is insoluble in water on the surface of the substrate to improve the bonding between the lubricating coating and the substrate.

[0053] The uniform dispersion process in step 2 specifically includes: weighing a certain amount of molybdenum disulfide / nano zinc oxide / borate composite lubricating material sample and dispersing it in a certain amount of dispersion solvent, ultrasonically treating it for 2 to 4 hours to form a uniformly mixed dispersion with a concentration of 0.1 mol / L, filtering the dispersion with filter paper, and directly putting the filtrate into a spray bottle for use.

[0054] The air spraying process in step 3 specifically includes: placing the substrate formed with the borate transition layer at 50-60°C, for example, 50°C, 53°C, 56°C, 60°C, etc.; preheating for 30-40min, for example, 30min, 33min, 36min, 40min, etc.; while maintaining the spray gun air pressure at 0.6-0.7MPa, the spray gun caliber of 1-2mm, placing the preheated substrate horizontally, and the spray gun 20-30cm away from the substrate, for example, 20cm, 23cm, 26cm, 30cm, etc.; the inclination angle is 40-60°, for example, 40°, 45°, 50°, 55°, 60°, etc.; the number of reciprocating times is 2-3 times, and the coating thickness is about 60μm.

[0055] Step 3 also includes: after the coating is prepared, placing the substrate at 60-80°C, for example, 60°C, 65°C, 70°C, 75°C, 80°C, etc.; drying in a vacuum drying oven for 40-60 minutes, for example, 40 minutes, 45 minutes, 50 minutes, 60 minutes, etc.; then transferring it to a muffle furnace for curing, the curing temperature is 180-200°C, for example, 180°C, 185°C, 190°C, 195°C, 200°C, etc.; the curing time is 60-80 minutes, for example, 60 minutes, 65 minutes, 70 minutes, 80 minutes, etc.; after naturally cooling to room temperature, a molybdenum disulfide / nano zinc oxide / borate composite lubricating coating is obtained.

[0056] The following is a detailed description in conjunction with specific embodiments. Example 1

[0057] MoS2 / nano ZnO was prepared by a one-step hydrothermal method: first, ammonium molybdate and thiourea with a molar ratio of 1:1 were dispersed in a certain amount of deionized water, stirred for 30 minutes using a magnetic stirrer, and ultrasonically treated for 30 minutes until completely dispersed. Then, a certain amount of ZnO nanoparticles (average particle size of 30±10nm) was added according to the molar ratio of ammonium molybdate and nano ZnO of 1:7, and then magnetic stirring was performed for 60 minutes, and ultrasonic treatment was performed for 60 minutes until the solution was fully mixed. Finally, the mixed solution was transferred to a 100mL polytetrafluoroethylene-lined stainless steel autoclave and stored in an oven at 200°C for 24 hours. After it was naturally cooled to room temperature, it was washed with anhydrous ethanol and deionized water several times, and the black precipitate was collected by filtration and centrifugation. Finally, it was vacuum dried at 60°C for 18 hours to obtain MoS2 / nano ZnO.

[0058] Preparation of MoS2 / Nano-ZnO / Borate Composite Lubricant: First, the prepared MoS2 / Nano-ZnO sample was ball-milled and mixed with sodium borate. The ball milling jar used was a stainless steel jar lined with tungsten carbide, the grinding medium was tungsten carbide carbide balls (5 mm), the ball-to-powder ratio was about 2:1, the rotation speed was 180 rpm, and the ball milling time was 6 hours. The obtained uniform powder was then dispersed in a dispersing solvent (ethylene glycol ethyl ether, xylene and acetone, etc.), and a uniform mixed solution was obtained by ultrasonic stirring for 6 hours. Then, it was thoroughly washed several times with deionized water and anhydrous ethanol, and finally vacuum dried at 80°C for 24 hours to obtain a MoS2 / Nano-ZnO / Borate composite lubricant.

[0059] Preparation of MoS2 / Nano-ZnO / Borate Composite Lubricating Coating:

[0060] (1) First, the substrate is surface pretreated. The 718 high-temperature alloy substrate is cut into 30*5*2mm substrates using wire cutting, and then polished with 200 mesh, 400 mesh, 600 mesh and 1000 mesh sandpaper until there are no scratches. Acetone and anhydrous ethanol are used to ultrasonically clean the substrate to remove oil and other impurities and dry it. The substrate is then subjected to surface sandblasting and borate treatment, that is, the surface roughness of the substrate is artificially increased and a water-insoluble borate transition layer is formed on the substrate surface to improve the bonding between the lubricating coating and the substrate.

[0061] (2) Secondly, the lubricant sample was pretreated. A certain amount of molybdenum disulfide / nano zinc oxide / borate composite lubricant sample was weighed and dispersed in a certain amount of dispersion solvent, and ultrasonically treated for 2 hours to form a uniformly mixed dispersion with a concentration of 0.1 mol / L. After filtering the dispersion with filter paper, the filtrate was directly put into a spray bottle for use.

[0062] (3) Finally, the coating was prepared by air spraying. The substrate pretreated in step (1) was preheated at 50°C for 40 minutes, while the spray gun air pressure was maintained at 0.6MPa and the spray gun caliber was 1mm. The preheated substrate was placed horizontally, the spray gun was 20cm away from the substrate, the tilt angle was 40°, the number of reciprocating times was 2 times, and the coating thickness was about 60μm. After the coating was prepared, the substrate was placed in a 60°C vacuum drying oven and dried for 60 minutes, and then transferred to a muffle furnace for curing. The curing temperature was 180°C and the curing time was 80 minutes. After naturally cooling to room temperature, a molybdenum disulfide / nano zinc oxide / borate composite lubricating coating was obtained. Example 2

[0063] MoS2 / nano ZnO was prepared by a one-step hydrothermal method: first, ammonium molybdate and thiourea with a molar ratio of 1:1 were dispersed in a certain amount of deionized water, stirred for 40 minutes using a magnetic stirrer, and ultrasonically treated for 20 minutes until completely dispersed. Then, a certain amount of ZnO nanoparticles (average particle size of 30±10nm) was added according to the molar ratio of ammonium molybdate and nano ZnO of 1:8, and then magnetic stirring was performed for 70 minutes, and ultrasonic treatment was performed for 50 minutes until the solution was fully mixed. Finally, the mixed solution was transferred to a 100mL polytetrafluoroethylene-lined stainless steel autoclave and stored in an oven at 210°C for 24 hours. After it was cooled naturally to room temperature, it was washed with anhydrous ethanol and deionized water several times, and the black precipitate was collected by filtration and centrifugation. Finally, it was vacuum dried at 70°C for 15 hours to obtain MoS2 / nano ZnO.

[0064] Preparation of MoS2 / Nano-ZnO / Borate Composite Lubricating Material: First, the prepared MoS2 / Nano-ZnO sample is ball-milled and mixed with borate (sodium borate, potassium borate, etc.). The ball milling jar used is a stainless steel jar lined with tungsten carbide, the grinding medium is tungsten carbide carbide ball (5mm), the ball-to-powder ratio is about 2:1, the rotation speed is 270rmp, and the ball milling time is 5 hours. Then the obtained uniform powder is dispersed in a dispersing solvent (ethylene glycol ethyl ether, xylene and acetone, etc.), and a uniform mixed solution is obtained by ultrasonic stirring for 7 hours. Then it is thoroughly washed several times with deionized water and anhydrous ethanol, and finally vacuum dried at 90°C for 20 hours to obtain MoS2 / Nano-ZnO / Borate Composite Lubricating Material.

[0065] Preparation of MoS2 / Nano-ZnO / Borate Composite Lubricating Coating:

[0066] (1) First, the substrate is surface pretreated. The 718 high-temperature alloy substrate is cut into 30*5*2mm substrates using wire cutting, and then polished with 200 mesh, 400 mesh, 600 mesh and 1000 mesh sandpaper until there are no scratches. Acetone and anhydrous ethanol are used to ultrasonically clean the substrate to remove oil and other impurities and dry it. The substrate is then subjected to surface sandblasting and borate treatment, that is, the surface roughness of the substrate is artificially increased and a water-insoluble borate transition layer is formed on the substrate surface to improve the bonding between the lubricating coating and the substrate.

[0067] (2) Secondly, the lubricant sample was pretreated. A certain amount of molybdenum disulfide / nano zinc oxide / borate composite lubricant sample was weighed and dispersed in a certain amount of dispersion solvent, and ultrasonically treated for 3 hours to form a uniformly mixed dispersion with a concentration of 0.1 mol / L. After filtering the dispersion with filter paper, the filtrate was directly put into a spray bottle for use.

[0068] (3) Finally, the coating was prepared by air spraying. The substrate pretreated in step (1) was preheated at 55°C for 35 minutes, while the spray gun air pressure was maintained at 0.65MPa and the spray gun caliber was 1.5mm. The preheated substrate was placed horizontally, the spray gun was 25cm away from the substrate, the tilt angle was 45°, the number of reciprocating times was 2 times, and the coating thickness was about 60μm. After the coating was prepared, the substrate was placed in a 70°C vacuum drying oven for 50 minutes, and then transferred to a muffle furnace for curing. The curing temperature was 190°C and the curing time was 70 minutes. After naturally cooling to room temperature, a molybdenum disulfide / nano zinc oxide / borate composite lubricating coating was obtained. Example 3

[0069] MoS2 / nano ZnO was prepared by a one-step hydrothermal method: first, ammonium molybdate and thiourea with a molar ratio of 1:1 were dispersed in a certain amount of deionized water, stirred for 50 minutes using a magnetic stirrer, and ultrasonically treated for 10 minutes until completely dispersed. Then, a certain amount of ZnO nanoparticles (average particle size of 30±10nm) was added according to the molar ratio of ammonium molybdate and nano ZnO of 1:9, and then magnetic stirring was performed for 80 minutes, and ultrasonic treatment was performed for 40 minutes until the solution was fully mixed. Finally, the mixed solution was transferred to a 100mL polytetrafluoroethylene-lined stainless steel autoclave and stored in an oven at 220°C for 24 hours. After it was naturally cooled to room temperature, it was washed with anhydrous ethanol and deionized water several times, and the black precipitate was collected by filtration and centrifugation. Finally, it was vacuum dried at 80°C for 12 hours to obtain MoS2 / nano ZnO.

[0070] Preparation of MoS2 / Nano-ZnO / Borate Composite Lubricating Material: First, the prepared MoS2 / Nano-ZnO sample is ball-milled and mixed with borate (sodium borate, potassium borate, etc.). The ball milling jar used is a stainless steel jar lined with tungsten carbide, the grinding medium is tungsten carbide carbide ball (8mm), the ball-to-powder ratio is about 2:1, the rotation speed is 360rmp, and the ball milling time is 4 hours. Then the obtained uniform powder is dispersed in a dispersing solvent (ethylene glycol ethyl ether, xylene and acetone, etc.), and a uniform mixed solution is obtained by ultrasonic stirring for 8 hours. Then it is thoroughly washed several times with deionized water and anhydrous ethanol, and finally vacuum dried at 100°C for 18 hours to obtain MoS2 / Nano-ZnO / Borate Composite Lubricating Material.

[0071] Preparation of MoS2 / Nano-ZnO / Borate Composite Lubricating Coating:

[0072] (1) First, the substrate is surface pretreated. The 718 high-temperature alloy substrate is cut into 30*5*2mm substrates using wire cutting, and then polished with 200 mesh, 400 mesh, 600 mesh and 1000 mesh sandpaper until there are no scratches. Acetone and anhydrous ethanol are used to ultrasonically clean the substrate to remove oil and other impurities and dry it. The substrate is then subjected to surface sandblasting and borate treatment, that is, the surface roughness of the substrate is artificially increased and a water-insoluble borate transition layer is formed on the substrate surface to improve the bonding between the lubricating coating and the substrate.

[0073] (2) Secondly, the lubricant sample was pretreated. A certain amount of molybdenum disulfide / nano zinc oxide / borate composite lubricant sample was weighed and dispersed in a certain amount of dispersion solvent, and ultrasonically treated for 4 hours to form a uniformly mixed dispersion with a concentration of 0.1 mol / L. After filtering the dispersion with filter paper, the filtrate was directly put into a spray bottle for use.

[0074] (3) Finally, the coating was prepared by air spraying. The substrate pretreated in step (1) was preheated at 60°C for 30 minutes, while the spray gun air pressure was maintained at 0.7MPa and the spray gun caliber was 2mm. The preheated substrate was placed horizontally, the spray gun was 30cm away from the substrate, the tilt angle was 60°, the number of reciprocating times was 3 times, and the coating thickness was about 60μm. After the coating was prepared, the substrate was placed in an 80°C vacuum drying oven for 40 minutes, and then transferred to a muffle furnace for curing. The curing temperature was 200°C and the curing time was 60 minutes. After naturally cooling to room temperature, a molybdenum disulfide / nano zinc oxide / borate composite lubricating coating was obtained.

[0075] The detection method of the high temperature composite lubricating material obtained in Example 1 of the present invention is as follows:

[0076] The friction and wear properties were evaluated by the reciprocating mode of the friction and wear tester / LMT-100 (Rtec, America), the dual ball was a ceramic (Si3N4) ball, the temperature was from room temperature to 1000°C, the resolution was 0.1°C, the force sensor range was 2 to 200N, and the resolution was 0.6mN.

[0077] Test 1:

[0078] The dual ball is a ceramic (Si3N4) ball, the load is 10N, the frequency is 3Hz, the running time is 5min, and the experimental temperature is 750℃;

[0079] The friction coefficient of the MoS2 / nano ZnO / sodium borate high temperature composite lubricant is small, about 0.23, which can reduce the friction coefficient by more than 40% compared with the condition without lubrication. Figure 2 shown.

[0080] Test 2:

[0081] The dual ball is a ceramic (Si3N4) ball, the load is 10N, the frequency is 3Hz, the running time is 5min, and the experimental temperature is 775℃;

[0082] The friction coefficient of the MoS2 / nano ZnO / sodium borate high temperature composite lubricant is small, about 0.21, and compared with the unlubricated condition, the friction coefficient can be reduced by more than 45%. The friction coefficient curve is shown in the attached figure. Figure 3 shown.

[0083] Test 3:

[0084] The dual ball is a ceramic (Si3N4) ball, the load is 10N, the frequency is 3Hz, the running time is 5min, and the experimental temperature is 800℃;

[0085] The friction coefficient of the MoS2 / nano ZnO / sodium borate high temperature composite lubricant is small, about 0.16, which can reduce the friction coefficient by more than 60% compared with the condition without lubrication. Figure 4 shown.

[0086] It should be noted that, in this article, terms such as "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.

[0087] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a borate-introduced molybdenum disulfide / nano zinc oxide composite lubricating material, characterized in that: include: The MoS2 / nano ZnO composite material was prepared by a one-step hydrothermal method, and the process specifically includes: firstly, ammonium molybdate and thiourea with a molar ratio of 1:1 are dispersed in a certain amount of deionized water, stirred by a magnetic stirrer for 30 to 50 minutes, and ultrasonically treated for 10 to 30 minutes until the mixture is completely and evenly dispersed; then, a certain amount of ZnO nanoparticles are added according to a molar ratio of ammonium molybdate to nano ZnO of 1:7 to 9, magnetically stirred for 60 to 80 minutes, and ultrasonically treated for 40 to 60 minutes until the solution is fully mixed; finally, the mixed solution is transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, and stored in an oven at 200 to 220°C for 24 hours; After cooling to room temperature naturally, washing with anhydrous ethanol and deionized water for multiple times, collecting black precipitates by filtration and centrifugation; finally, vacuum drying at 60-80° C. for 12-18 hours to obtain a MoS2 / nano ZnO composite material; The MoS2 / nano ZnO composite material is ball-milled and mixed with a borate to obtain a uniform mixed powder, wherein the borate is one of sodium borate and potassium borate; Dispersing the uniformly mixed powder in a dispersion solvent, and stirring by ultrasonic for 6 to 8 hours to obtain a uniformly mixed solution, wherein the dispersion solvent is one of ethylene glycol ethyl ether, xylene and acetone; The uniformly mixed solution is washed and dried to obtain a molybdenum disulfide / nano zinc oxide / borate composite lubricating material.

2. The method for preparing the borate-introduced molybdenum disulfide / nano zinc oxide composite lubricating material according to claim 1, characterized in that: The parameters of the ball milling mixing are set as follows: the ball-to-powder ratio is 2:1, the rotation speed is 180-360 rpm, and the ball milling time is 4-6 hours.

3. The method for preparing the borate-introduced molybdenum disulfide / nano zinc oxide composite lubricating material according to claim 1, characterized in that: The ball milling jar for ball milling and mixing is a stainless steel jar lined with tungsten carbide, and the grinding medium is a tungsten carbide hard alloy ball.

4. The method for preparing the borate-introduced molybdenum disulfide / nano zinc oxide composite lubricating material according to claim 3, characterized in that: The diameter of the tungsten carbide hard alloy ball is 5 mm or 8 mm.

5. The method for preparing the borate-introduced molybdenum disulfide / nano zinc oxide composite lubricating material according to claim 1, characterized in that: The drying conditions are: vacuum drying at 80-100° C. for 18-24 hours.

6. A method for preparing a lubricating coating, characterized in that: include: The high-temperature alloy substrate that has undergone surface pretreatment is subjected to borate boration treatment to form a borate transition layer that is insoluble in water on the surface of the substrate; Uniformly dispersing the molybdenum disulfide / nano zinc oxide / borate composite lubricating material prepared by the preparation method of any one of claims 1 to 5 to obtain a uniformly mixed composite lubricating material dispersion; The composite lubricating material dispersion is air-sprayed to prepare a molybdenum disulfide / nano zinc oxide / borate composite lubricating coating.

7. The method for preparing a lubricating coating according to claim 6, characterized in that: The air spraying specifically comprises: The substrate with the borate transition layer is preheated at 50-60°C for 30-40 minutes, while the spray gun air pressure is maintained at 0.6-0.7MPa and the spray gun caliber is 1-2mm. The preheated substrate is placed horizontally, the spray gun is 20-30cm away from the substrate, the tilt angle is 40-60°, the number of reciprocating times is 2-3 times, and the coating thickness is 60μm.

8. The method for preparing a lubricating coating according to claim 7, characterized in that: The method further comprises: After the coating is prepared, the substrate is placed in a vacuum drying oven at 60-80°C for 40-60 minutes and then transferred to a muffle furnace for curing at a curing temperature of 180-200°C for 60-80 minutes. After naturally cooling to room temperature, a molybdenum disulfide / nano zinc oxide / borate composite lubricating coating is obtained.

Citation Information

Patent Citations

  • MXene composite nano material and preparation method and applications thereof

    CN110918108A

  • Preparation method of molybdenum disulfide composite nano-zinc oxide high-temperature lubricant

    CN116004300A